Additional file 2 of Menopause experience in First Nations women and initiatives for menopause symptom awareness; a community-based participatory research approach - Beate C. Sydora (10704521); Bonny Graham (10704524); Richard T. Oster (10704527); Sue Ross (791382) (2021)
Additional file 2. Menopause information for men.